Hydrogen-based metabolism as an ancestral trait in lineages sibling to the Cyanobacteria - Paula B. Matheus Carnevali; Frederik Schulz; Cindy J. Castelle; Rose S. Kantor; Patrick M. Shih; Itai Sharon; Joanne M. Santini; Matthew R. Olm; Yuki Amano; Brian C. Thomas; Karthik Anantharaman; David Burstein; et al. (Nature Communications, 2019)
Most cyanobacteria are oxygenic photoautotrophs, and fermenters under dark anoxic conditions. Here, the authors analyse genomic sequences of related uncultivated bacteria, inferring their metabolic potential, and supporting that their common ancestor was an anaerobe capable of fermentation and H2 metabolism.